Job Satisfaction as a Strategic Path for Employee Performance: The Role of Performance, Motivation, and Competency Assessment at KPP Pratama Kepanjen - Siwi Dyah Ratnasari; Anita Yushardini (Fakultas Ekonomi Universitas Kadiri, 2026)
Employee performance remains a critical issue in public-sector organizations because it reflects administrative accountability, service effectiveness, and institutional achievement. This study examines the mediating role of job satisfaction in the relationship between performance appraisal, motivation, competence, and employee performance at KPP Pratama Kepanjen. A quantitative explanatory research design was employed. The population consisted of all 76 employees of KPP Pratama Kepanjen, and the census technique was used to determine the respondents. Primary data were collected using a structured questionnaire measured on a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that performance appraisal and motivation have significant effects on job satisfaction, whereas competence does not significantly affect job satisfaction. Job satisfaction has a significant effect on employee performance. However, performance appraisal, motivation, and competence do not have direct significant effects on employee performance. The mediation analysis shows that job satisfaction significantly mediates the effect of motivation on employee performance, but does not mediate the effects of performance appraisal and competence on employee performance. These findings indicate that employee performance in a public-sector tax office is not merely determined by formal appraisal systems or individual competence, but also by psychological mechanisms that convert work motivation into job satisfaction. This study contributes to public-sector human resource management literature by demonstrating that job satisfaction is not a universal mediator, but a specific psychological pathway through which motivation can improve employee performance. Keywords: competence; employee performance; job satisfaction; motivation; Performance Appraisal